Extraoral Sinus Tracts of Odontogenic Origin: A Case Series - Ellahe Azizlou; Mohsen AminSobhani; Sholeh Ghabraei; Mehrfam Khoshkhounejad; Abdollah Ghorbanzadeh; Shima Saber Tahan (Tehran University of Medical Sciences, 2020)
Extraoral sinus tracts of odontogenic origin often develop as the result of misdiagnosis of persistent dental infections due to trauma, caries, or periodontal disease. Due to these lesions' imitation from cutaneous lesions, misdiagnosis, and mismanagement, which we frequently encounter, this article aims to describe four cases with manifestations in different parts of the face and the neck. Patients were referred to an endodontist with a history of several surgical procedures and/or antibiotic therapy due to misdiagnosis. After comprehensive examinations, root canal treatment was performed. The resolution of signs and symptoms during the follow-up period confirmed the correct diagnosis. Dermatologists and other physicians should be aware of the possibility of the relationship of extraoral sinus tracts with dental infections. Precise examination and taking a comprehensive history can aid to prevent unnecessary and incorrect therapeutic and/or pharmaceutical interventions. Elimination of dental infection leads to complete recovery in such patients.